2019
DOI: 10.1002/adma.201900390
|View full text |Cite
|
Sign up to set email alerts
|

A Thermodynamically Favored Crystal Orientation in Mixed Formamidinium/Methylammonium Perovskite for Efficient Solar Cells

Abstract: In the past few years, hybrid organic-inorganic perovskite solar cells (PSCs) have been widely investigated and the power conversion efficiency (PCE) rocket-boosted from 3.8% to 23.7%, [1] originating from the excellent properties of perovskite materials such as appropriate and adjustable bandgap, high absorption coefficient, good charge carrier mobility, long carrier diffusion length, low recombination rate, and high tolerance of chemical defects. [2] Among various compositions, hybrid organic-inorganic PSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 60 publications
5
120
0
Order By: Relevance
“…Controlling the crystal orientation to achieve rapid carrier transport can effectively avoid or reduce the adverse effects caused by the organic layer. [95][96][97] Further, the distribution of QW also affects the performance of 2D PSCs, and needed to well understanding.…”
Section: Crystallization Kineticsmentioning
confidence: 99%
“…Controlling the crystal orientation to achieve rapid carrier transport can effectively avoid or reduce the adverse effects caused by the organic layer. [95][96][97] Further, the distribution of QW also affects the performance of 2D PSCs, and needed to well understanding.…”
Section: Crystallization Kineticsmentioning
confidence: 99%
“…In addition, the effects of cation species (MA + , FA + , and Cs + ) in precursor solutions on the perovskite crystallization kinetics have been partly illustrated. For example, Xu and co‐workers reported that MA/FA cation ratio would affect the surface energy of the mixed perovskites, leading to the variation of preferential orientation in mixed‐cation perovskites …”
Section: Controlling Precursor Solution Characteristics For Perovskitmentioning
confidence: 99%
“…c) Crystal structures of three intermediate phases: PbI 2 ‐rich (MA) 2 (DMF) 2 Pb 3 I 8 , stoichiometric (MA) 2 (DMF) 2 Pb 2 I 6 , and MAI‐rich (MA) 3 (DMF)PbI 5 . Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Controlling Precursor Solution Characteristics For Perovskitmentioning
confidence: 99%
“…The facet orientation regulation has been considered as an effective route to elevate the device performance . 2D synchrotron radiation grazing incidence wide‐angle X‐ray scattering has been widely used to detect the crystal orientation . While, in order to clarify the relationship between grain orientation and photoelectric properties of perovskite at the same time, new representations are required.…”
Section: Applications Of C‐afm Techniquementioning
confidence: 99%